Note on Some Nonlinear Integral Inequalities and Applications to Differential Equations - Khaled Boukerrioua (International Journal of Differential Equations)
Using ideas from Boukerrioua and Guezane-Lakoud (2008), some nonlinear integral inequalities are established.